Opening Doors - Natalie Le Clue (Persona Studies)
Traditionally, political affiliation has proven to be one of the most fruitful mechanisms to create division and derision amongst the voting masses. So polarising is the topic of politics that it has coined its own phrase – political divide. Drawing from insights in fan studies, this article explores toxic fan practices within political fandom, as highlighted by Petersen et al. (2023) and Le Clue (2024). It examines the participation and practices of online users/fans within South African politics by focusing on the use of #voestsekanc via X (formerly Twitter) as a case study. In the constantly evolving landscapes of online communities, fan studies provides a lens to comprehend the complexity of participation and engagement, which can both empower and disempower individuals (Pearson 2010, p. 84). Despite this level of agency, the representation of African voices in fan studies is severely limited, which excludes the possibility of a comprehensive understanding of online dynamics within the African context. Therefore, this paper expands the scope of fan studies beyond Western perspectives and contributes to a more diverse scholarly discourse within this field of study.